LGBTQ+ librarianship in the 21st century : emerging directions of advocacy and community engagement in diverse information environments - Mehra, Bharat (Emerald Publishing Limited, 2019)
Libraries are at the heart of many of the communities they serve. Increasingly, it is important for them to adjust to serve minority groups, including LGBTQ+ communities. This collection presents original scholarship on the emerging directions of advocacy and community engagement in LGBTQ+ librarianship.With contributions from library and information professionals, this volume explores how librarians and library professionals can embrace a more proactive role as social justice advocates, and help promote fairness, justice, equality, equity, and activism on behalf of LGBTQ+ people. Starting within the library space, the volume offers an introduction to terminology and resources around LGBTQ+ information, before moving on to explore examples of how LGBTQ+ librarianship can adopt innovative approaches to better serve their patrons in select settings around the world. Including case studies on health services, historical archives, and LGBTQ+ homelessness, this collection dispels misperceptions and myths surrounding social justice research and is vital for any researcher or practitioner interested in supporting evolving communities.
Includes index.
Keywords: Libraries and gays.; Libraries and lesbians.; Human rights advocacy.; Language Arts & Disciplines -- Library & Information Science -- Administration & Management.; Library & information sciences.; elektronické knihy; electronic books